2021
DOI: 10.1111/jors.12563
|View full text |Cite
|
Sign up to set email alerts
|

Compact development and preferences for social mixing in location choices: Results from revealed preferences in Santiago, Chile

Abstract: Even though densification and social mixing are declared objectives of many nowadays urban planning paradigms, their simultaneous implementation is usually questioned by different actors and is not frequent in practice. In a market economy, understanding potential demand for this class of development, from different types of households, is essential to define public policies oriented to achieve both compact development (CD) and social mixture. To understand the preferences of households and potential demand, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…ey found that the influence of the independent variables like household income on ridership at most stations was spatially different [25]. To further investigate the spatialimpacts, Cox and Hurtubia used spatial regression models to count for the spatial autocorrelation [10,[32][33][34]. And one of the studies concluded that the usage of dockless bike stations was spatially autocorrelated in commercial areas and road intersections [31].…”
Section: Factors Influencingmentioning
confidence: 99%
See 1 more Smart Citation
“…ey found that the influence of the independent variables like household income on ridership at most stations was spatially different [25]. To further investigate the spatialimpacts, Cox and Hurtubia used spatial regression models to count for the spatial autocorrelation [10,[32][33][34]. And one of the studies concluded that the usage of dockless bike stations was spatially autocorrelated in commercial areas and road intersections [31].…”
Section: Factors Influencingmentioning
confidence: 99%
“…Despite their wide use, they do not capture the spatial variation in the relationship between predictor and response variables, especially in the case of large study areas [8,9]. erefore, the spatial latent class model [10] and the geographically weighted regression (GWR) models [7] are some of the methods adopted to capture this spatial variation. In this study, the GWR model is used.…”
Section: Introductionmentioning
confidence: 99%